(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article explores innovative approaches and technologies transforming warehouse systems. Emphasis is placed on automation, artificial intelligence (AI), Internet of Things (IoT), and data analytics. The integration of these technologies enhances efficiency, accuracy, and cost-effectiveness in warehousing operations. Key challenges and future research directions are also discussed.